TAM: A Reference Model For Mobile Cash Adoption - Bayona Orè, Sussy (2017)
Several theories of adoption models have been developed. All of them have different constructs depending on their application. Select a model is a difficult task because all of them have strong behavioural elements. In this paper a method of model selection is presented. The method was applied in order to select the most suitable model for an application related to device "Mobile Cash" technology. The method is based on four steps that are described in detail. The adoption models were evaluated based on eight criterions. In this article, shall be discussed each behavioral model such as TAM, IDT, TPB among others, and as a result the TAM model was selected. Finally, a model for Mobile Cash Adoption using TAM is present.